1996
DOI: 10.1029/95wr03486
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Reservoir Density Underflow And Interflow From A Chemical Spill

Abstract: An integral simulation model has been developed for understanding and simulating the process of a density current and the transport of spilled chemicals in a stratified reservoir. The model is capable of describing flow behavior and mixing mechanisms in different flow regimes (plunging flow, underflow, • and interflow). It computes flow rate, velocity, flow thickness, mixing parameterized by entrainment and dilution, depths of plunging, separation and intrusion, and time of travel. The model was applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…Gu et al (1996) and Gu and Chung (1998; used various simulation models (1D integral model, 2D mixing-length model, and code CE-QUAL-W2) to investigate the density current in a thermally stratified environment. They studied the effects of inflow boundary conditions, ambient stratification, and geometry on the behavior of a density current, and found that an inverse relationship exists between ambient stratification and interflow travel time.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al (1996) and Gu and Chung (1998; used various simulation models (1D integral model, 2D mixing-length model, and code CE-QUAL-W2) to investigate the density current in a thermally stratified environment. They studied the effects of inflow boundary conditions, ambient stratification, and geometry on the behavior of a density current, and found that an inverse relationship exists between ambient stratification and interflow travel time.…”
Section: Introductionmentioning
confidence: 99%
“…For the reservoir with shallow water basin the aspect ratio of vertical to horizontal scale is rather small, thus the assumption of hydrostatic pressure equation is proposed and justified by the excessive studies by King (1985a,b). For lakes or reservoirs with small aspect ratio in width/length dimension, a laterally averaged two-dimensional model (Buchak and Edinger, 1982;King, 1985a;Karpik and Raithby, 1990;Gu et al" 1996;Choi, 1998;Chung and Gu, 1998) can be used to study the density currents in the longitudinal-vertical cross section which is vital to the modeling of the hydrothermal structure. If the objective of the study is only limited to determine the vertical temperature profile of the lake/reservoir, where measurements are not avail able, a simple one-dimensional model can be described using the energy equation for the water column (Hondzo and Stefan, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…연구결과 dp, Xp, ds, Chung and Gu, 1998 (Fischer et al, 1979;Chung and Gu, 1998). 상층류의 형태로 흐르던 유입수는 흐름에 의한 운동량과 음부력 이 같아지는 지점에서 저수지 수면 아래로 침강하게 되 며, 이러한 현상이 일어나는 지점을 침강점이라고 한다 (Fischer et al, 1979;Ford and Johnson, 1981; (Baker and Paulson, 1981), DeGray 호수 (Ford and Johnson, 1981) 그리고 Wellington 저수지 (Hebbert et al, 1979) 등에서 현장실험이 이루어 졌으며, Alavian (1986), Johnson et al (1987Johnson et al ( , 1989 (1) et al(1989) 1.8 -21 > 10,000 Laboratory study Stefan and Johnson(1989) 3.0 -4.0 530,000 Field study, wastewater effluent Gu et al(1996) Table 1에 정리하였다. CE-QUAL-W2 dp(m) dp ( 값이 dp/ho보다 작거나 유사한 값을 보이고 있다.…”
unclassified